HADHANAH (CHILD CUSTODY) IN INDONESIAN SCHOOLS OF THOUGHT AND JURISPRUDENCE - Bagus Wahyuda Utama; Muhammad Amar Adly (AS-SAIS (JURNAL HUKUM TATA NEGARA/SIYASAH), 2026)
Hadhanah or child custody is one of the most sensitive and complex issues in Islamic family law, especially after divorce. This study aims to analyze the concept of hadhanah from the perspective of the four schools of jurisprudence (Hanafi, Maliki, Shafi'i, and Hanbali) and examine its application in the decisions of Indonesian Religious Courts. This research employs a normative juridical method with a comparative approach and verdict analysis. The findings reveal significant differences in custodian priority order and the age limits of children among the schools, yet all four agree that the best interests of the child (mashlahah al-walad) is the primary criterion. Indonesian Religious Courts, through the Compilation of Islamic Law and Supreme Court jurisprudence, tend to integrate the principle of the best interest of the child with madhab norms, resulting in adaptive and contextual decisions.Keyword: Hadhanah; Child Custody; Schools of Jurisprudence; Jurisprudence; Best Interest of the Child.